Ultraviolet photodissociation spectra of singly protonated hexapeptides DYYVVR, DYFVVR, and DFYVVR at room temperature - Jeon, Hyo Nam; Kwon, Jang Han; Kang, Hyuk (Bulletin of the Korean Chemical Society, 2023)
DYYVVR is a tryptic peptide of Janus kinase 3 and has the two active tyrosine residues needed for the regulation of the protein's activity by phosphorylation. As a proof-of-concept experiment for localization of phosphorylation site, two-dimensional ultraviolet-mass spectrometry of singly protonated DYYVVR has been investigated at room temperature. Comparing the absorption spectrum with those of peptides with single phenylalanine substitution, DYFVVR and DFYVVR, it is confirmed that the ultraviolet (UV) absorption below 35 100 cm−1 is due to the first tyrosine residue. Combined with the fact that the absorption of a phosphorylated tyrosine is shifted above 37 500 cm−1, two-dimensional analysis employing mass spectrometry and ultraviolet spectroscopy can be used as a tool for localization of phosphorylation site in a peptide.
Keywords: Hexapeptides; Ion spectroscopies; JAK3; Localisation; Phosphorylation sites; Post-translational modifications; Protonated; Spectra's; Tyrosine residues; Ultraviolet photodissociation; ion spectroscopy; JAK3; mass spectrometry; phosphorylation; post-translational modification